2017
DOI: 10.13075/ijomeh.1896.00912
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorations of pulmonary function, elevated carbon monoxide levels and increased oxidative stress amongst water-pipe smokers

Abstract: This study has shown that water-pipe smoking leads to deterioration in pulmonary function and increases oxidative stress. To the best of our knowledge this study is the only one that has shown the effect of water-pipe smoking on oxidative stress. More studies must be planned to show the side effects of water-pipe habit and protective policies should be planned especially for young people in Europe. Int J Occup Med Environ Health 2017;30(5):731-742.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…OSI assesses the global oxidant/antioxidant balance in the living organisms [ 83 ]. It was decreased by the MGF and MF treatments, and this was correlated positively with TOS and negatively to TAR.…”
Section: Discussionmentioning
confidence: 99%
“…OSI assesses the global oxidant/antioxidant balance in the living organisms [ 83 ]. It was decreased by the MGF and MF treatments, and this was correlated positively with TOS and negatively to TAR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have examined the harmful effects of the hookah on the respiratory tract and the possible mechanisms that take place have focused mainly on the lower respiratory tract. The mechanisms that may be involved in respiratory diseases related to hookah smoking have been explored in previous studies 23 . Hookah smoking resulted in increased airway resistance, inflammation, oxidative stress and catalase activity in the lungs of animals 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Short-term effects may develop after short use of smoking. Several studies have shown that even a single WPS session lasting 30 min results in decreases in forced expiratory flow and other pulmonary functions, along with increases in blood pressure, heart rate, respiratory rate and carboxyhaemoglobin levels [31,32]. Respiratory symptoms develop after exposure to WPS.…”
Section: Health Effects Of Wpsmentioning
confidence: 99%